Flash sintering of hydroxyapatite ceramics. Issue 1 (2nd January 2021) - Hwang, Changhun; Yun, Jondo
ABSTRACT: The flash sintering process has been regarded as a noble method to densify ceramic materials. The distinctive feature of the flash sintering is the reduced sintering time which is caused by the electric field. In this study, flash sintering of the hydroxyapatite bioceramics was carried out at temperatures of 900–1200°C and electric fields of 500–1200 V/cm. Dense sintered sample was prepared in a short time within 10 seconds. Electric field required for flashing became reduced as the furnace temperature increased. Abrupt rise of the sample temperature of up to 120°C was observed when the flash occurred. The incubation time for flashing became shorter with increasing temperature and electric field. The flashing was found to occur at lower temperature and lower electric field in vacuum than in air. Microstructure of the flash sintered sample was not different from that of conventionally sintered sample.